1997
DOI: 10.1542/peds.100.3.e7
|View full text |Cite
|
Sign up to set email alerts
|

Hemoptysis: A 10-Year Retrospective Study

Abstract: ABSTRACT. Background. Hemoptysis is uncommon in pediatric practice. We reviewed 10 years of experience with hemoptysis in a tertiary pediatric hospital to identify patient characteristics and predictors of mortality.Methods. Patients were divided into four age groups (0 to 5, 6 to 10, 11 to 20, and >20 years). Hemoptysis was defined as mild (<150 mL/day), large (150 to 400 mL/day), or massive (>400 mL/day). Fever was defined as 38.5°C.Results. A total of 228 patients (115 males and 113 females) with 246 episod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
54
1
11

Year Published

2002
2002
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 84 publications
(68 citation statements)
references
References 30 publications
2
54
1
11
Order By: Relevance
“…Hemoptysis is uncommon in pediatric patients. Coss-Bu et al 3 reviewed 228 children and young adults over a period of 10 years, and found that cystic fibrosis was the major cause of hemoptysis in 65%, various types of congenital heart diseases in 16%, and other causes, including infections, in the rest. Among other causes, they found tuberculosis in only two patients (0.9%).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Hemoptysis is uncommon in pediatric patients. Coss-Bu et al 3 reviewed 228 children and young adults over a period of 10 years, and found that cystic fibrosis was the major cause of hemoptysis in 65%, various types of congenital heart diseases in 16%, and other causes, including infections, in the rest. Among other causes, they found tuberculosis in only two patients (0.9%).…”
Section: Discussionmentioning
confidence: 99%
“…Among other causes, they found tuberculosis in only two patients (0.9%). 3 Salazar et al found that 12% of definite pediatric pulmonary tuberculosis manifested with hemoptysis. 7 Although hemoptysis may be a presenting symptom of pulmonary tuberculosis in older children and adults, it is usually associated with other symptoms such as prolonged cough.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…2,6,7 In 1990s, cystic fibrosis and congenital heart diseases (mitral stenosis) were reported as predominant etiologic factors for hemoptysis. 8 Currently, various etiologies are suggested including idiopathic pulmonary hemosiderosis, pulmonary vascular malformation, pulmonary arteriovenous fistula, bronchiectasis, pulmonary tuberculosis, and lung tumors, with cystic fibrosis accounting for only 5% of cases. 9 Extrapulmonary bleeding, sometimes referred as pseudohemoptysis, is a common umbrella term for all types of hemorrhage not derived from the lungs or bronchial tubes and excluding hematemesis.…”
Section: Researchmentioning
confidence: 99%
“…Konjenital kalp hastalıkları (KKH) diğer bir hemoptizi nedenidir. Üçüncü basamak tedavi merkezlerinde gö-rülen tüm hemoptizi nedenlerinin %25'ini oluşturur [10]. KKH olan çocukların %4,5'i acil servise hemoptizi ile başvurur [11].…”
unclassified